Prevalence of C-ducts of Mandibular Second Molars Evaluated on Cone Beam Tomography - Rosa Verónica Castillo Córdova; Natalia Antuané León Ruidías; Alexander Roger Espinoza Salcedo; Paul Martín Herrera-Plasencia (Editorial Ciencias Médicas, 2024)
Introduction: Adequate knowledge of the configuration of root canals is fundamental in endodontics; tomographic evaluation allows a correct assessment of their radicular arrangement. Objective: To determine the prevalence of C-shaped canals in mandibular second molars, evaluated by cone beam tomography. Methods: A descriptive and cross-sectional study was carried out; the sample consisted of 200 permanent mandibular second molars from a Peruvian population, observed in cone beam tomography, where the presence of the C-shaped canal, its configuration according to Fan's classification and the patient's gender were recorded. Results: The prevalence of the C-shaped root canal configuration in lower second molars was 65.5%; according to the Fan classification, the highest prevalence was observed in the cervical third of the root canal, type C1 with 85.7%; in the middle third, type C2 with 42.9%; at the apical level it was type C3C with 72.1%; according to gender, 65.2% of the C-shaped canals corresponded to females. Conclusion: The prevalence of C-shaped canals in mandibular second molars evaluated in cone beam tomography was 65.5% with a higher predominance in the female gender. The tomographic evaluation allows a better identification and internal configuration of the root canals.